A collective coupled-channel model and mirror state energy displacements - Fraser, Paul; Amos, K.; Canton, L.; Karataglidis, S.; van der Knijff, D.; Svenne, J. (Springer New York LLC, 2015)
© 2015, SIF, Springer-Verlag Berlin Heidelberg. The spectra of nucleon-nucleus mirror systems allow examination of charge symmetry breaking in nucleon-nucleus interactions. To date, such examination has been performed with studies using microscopic models of structure. Herein we seek characterisation with a coupled-channel model in which the nucleon-nucleus interactions are described using a collective model prescription with the Pauli principle taken into account. The neutron-nucleus Hamiltonian is chosen to give the best match to the compound system spectrum, with emphasis on finding the correct ground state energy relative to the neutron-nucleus threshold. The Coulomb interactions for the proton-nucleus partner of a mirror pair are determined using charge distributions that match the root-mean-square charge radii of the nuclei in question. With the Coulomb interaction so defined modifying the neutron-nucleus Hamiltonian, we then predict a spectrum for the relevant proton-nucleus compound. Discrepancies in that resulting spectrum with measured values we tentatively ascribe to charge-symmetry breaking effects. We consider spectra obtained in this way for the mirror pairs 13C and 13N, 15C and 15F, and 15O and 15N, all to ~ 10 MeV excitation.